A future application environment for BC Hydro's EMS. - Vaahedi, E.
The paper reports on the results of a tailored collaboration project sponsored by BC Hydro and EPRI to review the state-of-the-art in EMS architectures addressing the necessary attributes of a modern EMS with respect to scalability, database and user interface openness, flexibility and conformance to industry standards, as well as to provide a migration path for the existing BC Hydro's EMS. This review was intended to assist BC Hydro in identifying functionality and standard requirements of future EMS procurements and a migration path for a future BC Hydro application program environment. The proposed migration path was prototyped to verify its prudence and applicability in providing an open architecture environment for EMS applications. The BC Hydro On-Line Voltage Stability Analysis (OLVSA) application developed by BC Hydro and Powertech Labs was chosen and integrated into the prototype
Keywords: BC Hydro; BC Hydro On-Line Voltage Stability Analysis; EMS; EPRI; Powertech Labs; XEMS; Common information model; Data exchange; Database; Energy management systems; Flexibility; Industry standards conformance; Migration path; Scalability; State-of-the-art.; Tailored collaboration project; User interface openness